Health Problems and Health Care Needs among Thai Elderly: Policy Recommendations - Kumsuchat, Supada (Journal of Health Science of Thailand, 2017)
Ageing society in Thailand leads to an increase of health problems and heath needs among Thai elderly people. Thai population will meet almost one fourth of total population in 2028. This article aimed to study elderly situation, health problems, health care needs, as well as policy recommendations for elderly health care provision in the future. The study showed that 56.5 percent were early elderly (60-69 years), 29.9 percent were middle elderly (70-79 years), and 13.6 percent were late elderly (80 years and above). It also showed that 79.5 percent were active ageing, 19.0 percent were home bound elders; and 1.5 percent were bed bound elders. Health situation of Thai elderly was found in moderate level. Health problems among the elderly were chronic diseases such as hypertension, diabetes, and cardiovascu lar diseases. Mobility disability, hearing impairment, and vision disability were three main disabilities found. These problems need to be cared. Government health care provision has not yet covered the target population. Policy recommendations to meet the health care needs of the elderly include job employment of retired health personnel in sub-district health promotion hospitals, increase elderly's subsistence allow ance, senior school promotion, criteria setting for selecting the elderly's family member to be trained as a post hospitalized elderly caretaker, set a skillful training curriculum for village health volunteers, elderly day care center promotion in local government authorities, and promotion of elderly care center and production of elderly care personnel in private sectors